Sociolinguistic Phenomena in Arabic Language Learning Through Direct Method - Moh. Munir (Jurnal Alsinatuna, 2022)
This study was aimed at analyzing the sociolinguistic phenomena during the implementation of the direct method in Arabic language learning at PP Al Iman Putri. The method used in this study was a case study method with a qualitative approach. The results of this study reveal that the sociolinguistics contributes to language learning, i.e., sociolinguistics as is a sub-discipline that studies language related to social factors to be the main provision for students when they pursue their studies in Middle Eastern countries. Sociolinguistics phenomena found in learning Arabic through the direct method were carried out by the means of various linguistic activities i.e., morning dialogue activity, correction of incorrect or inappropriate vocabularies, Arabic speech, learning activities using Arabic (with direct method), language court program (a program held by language department to punish those who do not use Arabic in their daily communication), Arabic drama, Arabic story telling, news reading in Arabic, Arabic vocabulary, and competition of nahwu and sharf (Arabic grammar) and mahfudzat.